Where and what? Frugivory is associated with more efficient foraging in three semi-free ranging primate species. Issue 5 (1st May 2019) - Trapanese, Cinzia; Robira, Benjamin; Tonachella, Giordana; di Gristina, Silvia; Meunier, Hélène; Masi, Shelly
Abstract : Foraging in seasonal environments can be cognitively challenging. Comparative studies have associated brain size with a frugivorous diet. We investigated how fruit distribution ( where ) and preference ( what ) affect foraging decisions in three semi-free ranging primate species with different degrees of frugivory: Macaca tonkeana ( N indiv = 5; N trials = 430), M. fascicularis ( N indiv = 3; N trials = 168) and Sapajus apella ( N indiv = 6; N trials = 288). We used 36 boxes fixed on trees and filled with highly and less preferred fruits with different (weekly) spatio-temporal distributions. Individuals were tested in two conditions: (1) same fruit provided concurrently in the same quantity but in a scattered and in a clumped distribution, (2) highly preferred fruit was scattered while the less preferred was clumped. Generally, primates preferred feeding first on the boxes of the clumped distribution in both conditions, with the more frugivorous species at a higher degree than the less frugivorous species in condition (1), but not (2). Therefore, what fruit was available changed the foraging decisions of the more frugivorous species who also engaged more in goal-directed travel. When feeding on preferred fruit, primates probably maximized foraging efficiency regardless of their degree of frugivory. Our findings emphasize that the food type and distribution may be a preponderant driver in cognitive evolution.